Predictive value of intraoperative electrocorticograms in resective epilepsy surgery - McBride, M C; Binnie, C D; Janota, I; Polkey, C E (Annals of neurology, 1991)
The preresection and postresection intraoperative electrocorticograms of 76 consecutive patients undergoing resective surgery for intractable epilepsy were analyzed to see if location, configuration, and discharge rate of epileptiform activity correlated with type and location of pathology of the resected specimens and outcome in regard to seizure control. The location of the predominant spike focus did not correlate with either type of location of pathology or with seizure outcome from temporal lobe surgery (n = 58). The presence of spontaneous or activated spikes outside the resected area did not correlate with outcome from any surgery type. Positive spikes recorded from the amygdala and anterior hippocampus (n = 37) were not associated with type or location of pathology, but bursts of fast repetitive spikes on these needle recordings tended to associate with mesiotemporal pathology (p = less than 0.02) and with mesial temporal sclerosis (p = less than 0.04). A preresection spike discharge rate of 1 per 4 minutes or less was associated with a poor outcome in 5 of 6 patients (p = 0.03), whereas a rate of 18 or more per minute was associated with a good outcome in 15 of 18 patients (p less than 0.06). Persistence of 50% or more of the preresection epileptiform activity in the postresection electrocorticogram after temporal lobectomy correlated with poor outcome in 80% (p = less than 0.03), although the absolute amount of epileptiform activity remaining in the postresection electrocorticogram did not correlate with outcome. Further studies are needed to define the role of intraoperative electrocorticograms in resective epilepsy surgery.